Parametric study of the reactive ion etching of silicon - Sotto, Romelyn H. (2008)
The demand for smaller yet faster and more powerful tools has been the primary driving force for device miniaturization and ultra large scale integration. As the density of device components increases, so does the device complexity. To keep pace with the technological requirements, stricter process control and more precise instrumentation are required. This study focused on one of the most critical device fabrication steps that puts the limit on the smallest feature that can be obtained-the etching process. The reactive ion etching process has practically replaced wet etching methods in ?critical? fabrication tasks where feature dimensions are less than 2 microns.